2005
DOI: 10.3201/eid1101.040835
|View full text |Cite
|
Sign up to set email alerts
|

Border Screening for SARS

Abstract: Screening at national borders may not be effective in controlling SARS spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
118
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 5 publications
3
118
0
Order By: Relevance
“…In Canada, 4 million travelers were screened, but none of five infected travelers were detected. Notably, none were symptomatic [20]. In Singapore, no cases were found among the 400,000 travelers that were screened [21].…”
Section: Exit and Entry Screeningmentioning
confidence: 83%
See 1 more Smart Citation
“…In Canada, 4 million travelers were screened, but none of five infected travelers were detected. Notably, none were symptomatic [20]. In Singapore, no cases were found among the 400,000 travelers that were screened [21].…”
Section: Exit and Entry Screeningmentioning
confidence: 83%
“…Since the case rate was very low and cases were difficult to detect, investing in health facilities' capacities to respond to cases and ensuring they obtain travel histories was considered more effective [20]. A modeling study concluded that entry screening might identify an estimated 9% of SARS cases in England, and would not significantly affect introduction [19].…”
Section: Exit and Entry Screeningmentioning
confidence: 99%
“…Such screening may take place at hospital entry, mainly in the emergency department, or at airports to detect travelers with increased body temperatures (1)(2)(3). Infrared thermal imaging devices have been proposed as a noncontact and noninvasive method for detecting fever (4)(5)(6).…”
mentioning
confidence: 99%
“…Fever screening is conducted at public places exposed to the outdoors (Bell and World Health Organization Working Group on International and Community Transmission of SARS 2004;Samaan et al 2004;St John et al 2005). Devices used to measure body temperature such as thermography, infrared skin thermometers, axillary thermometers, oral thermometers, and ear thermometers, may be affected by environmental factors in different ways (McCaffrey et al 1979;Burnham et al 2006).…”
mentioning
confidence: 99%